Social and ethical considerations for agricultural robotics - Ayris, Kirsten (Burleigh Dodds Series in Agricultural Science, 2023)
The scaling of agricultural robotics could help us to achieve sustainable agricultural transitions around the world, solving production, environmental, and socio-political challenges. Yet, for all the promises, there are social and ethical aspects to consider before pursuing pathways towards development and implementation. This chapter uses a responsible innovation framework to anticipate the possible challenges involved in the scaling of agricultural robotics, as well as how to include a wide range of stakeholder views. We discuss which stakeholders should be included in setting trajectories for agri-robotics, as well as how to engage harder to reach voices in a meaningful way. We then turn to how these stakeholder views can be reflexively incorporated into responsive practices, such as standards and codes of practice, to mitigate against some of the potential negative impacts of robotics.